THE PROBLEM OF LANGUAGE TEACHERS IN ONLINE LEARNING DURING THE PANDEMIC AN ANALYSIS OF TEACHING DISCOURSE IN SCHOOLS - Ulinsa, Ulinsa; Rinaldi, Rinaldi; Oringo, Vincent (Journal of Pragmatics and Discourse Research, 2021)
The  problems  in  the  research  are  how  problematic  language  teachers  are  in  online  learning  during  the  pandemic,  and  how  to  solve  problems  for  Indonesian  language  teachers  in  online  learning  during  the  pandemic.  The  purpose  of  this  study  is  to  describe  the  problems  of  Indonesian  language  teachers  in  online  learning  during  the  pandemic  and  to  describe  problem  solving  solutions  for  Indonesian  language  teachers  in  online  learning  during  the  pandemic.  This  research  is  a  qualitative  descriptive  research.  This  type  of  research  does  not  have  a  comparison  group.  The  subjects  in  this  study  were  Indonesian  language  teachers  at  SMP  and  SMA  Negeri  1  Ampibabo  in  Ampibabo  village.  Data  collection  in  this  study  were  questionnaires,  interviews  and  documentation.  The  data  from  the  evaluation  were  analyzed  using  qualitative  data  analysis  methods.  The  results  of  this  study  are  (1)  Inadequate  internet  network  access  during  the  online  learning  process.  (2)  The  teacher  is  a  "debt  collector"  in  carrying  out  the  online  teaching  and  learning  process,  the  teacher  only  gives  assignments  continuously  and  collects  assignments  at  a  predetermined  time.  (3)  Teachers  still  stutter  in  mastering  technology  so  that  in  the  implementation  of  online  learning  it  is  still  difficult  to  choose  relevant  applications  and  teaching  methods  are  still  not  varied.  (4)  The  implementation  of  online  learning  greatly  affects  the  psychological  condition  of  students  where  in  online  learning  these  students  experience  boredom  and  are  lazy  to  participate  in  learning.  The  teacher's  practical  solution  in  implementing  online  learning  is  by  applying  offline  learning  by  visiting  from  home  to  home  where  in  the  offline  learning  process  students  are  very  active  in  the  learning  process  compared  to  online  learning  which  cannot  be  carried  out  effectively